2013 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2013
DOI: 10.1109/ceidp.2013.6748312
|View full text |Cite
|
Sign up to set email alerts
|

Electrical tracking characterization of LLDPE-Natural Rubber blends filled with nanofillers

Abstract: Electrical tracking is a process of formation of permanent conducting path across the insulating material due to the surface erosion under high voltage application. The existing of leakage current (LC) on the wet contaminated material surface causes the generation of surface discharges that resulted to the material degradation. Electrical tracking test can be indicated as failure when LC exceed 60 mA for more than two seconds or at least 25mm of formation of carbon track or erosion breaks through the thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In the study, they concluded that different blend compositions as well as surface physical conditions affected leakage current and discharges, which further influenced the electrical tracking performance of the TPE blends. Jamail et al reported further investigation on the electrical tracking performance of the LLDPE/NR blend by adding silica and titania nanofiller at different concentrations. The results showed that the tracking resistance of LLDPE/NR improved with the presence of nanofiller, where sample with 1 wt% titania showed the lowest average leakage current, and exhibited the highest resistance to electrical tracking.…”
Section: The Emergence Of Thermoplastic Elastomer In Electrical Insulmentioning
confidence: 99%
“…In the study, they concluded that different blend compositions as well as surface physical conditions affected leakage current and discharges, which further influenced the electrical tracking performance of the TPE blends. Jamail et al reported further investigation on the electrical tracking performance of the LLDPE/NR blend by adding silica and titania nanofiller at different concentrations. The results showed that the tracking resistance of LLDPE/NR improved with the presence of nanofiller, where sample with 1 wt% titania showed the lowest average leakage current, and exhibited the highest resistance to electrical tracking.…”
Section: The Emergence Of Thermoplastic Elastomer In Electrical Insulmentioning
confidence: 99%
“…The results of electrical tracking resistance and leakage current of Linear Low-Density Polyethylene with Natural Rubber (LLDPE/NR) nanocomposites with silicone oxide (SiO 2 ) and titanium dioxide (TiO 2 ) nano fillers were reported in [17]. It was clear that low leakage current means less development of carbon tracks.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental test on the same composition of sample A3 was conducted by other researchers and they found that this composition shows lowest LC and no carbon track formation. [5]. However, simulation results also show that sample A1, A3 and A5 have a good resistance in tracking and erosion test due to the lowest current density and electric field distribution of range of 0.285 to 0.286 A/cm 2 and 1.09 to 1.10 kV/cm, respectively.…”
Section: Analysis On Sample With Different Loading Nanofillermentioning
confidence: 87%
“…To study the electrical performances of polymeric insulating materials, LC measurement are used as the tools to indicate the deterioration of the materials [4,5].The online monitoring of LC has been developed by previous researchers and this LC are acquired throughout the duration of six-hour [6][7][8]; Indeed, the obtained LC are proportional to degradation of polymer materials [9,10]. The influence of contaminant conductivity was studied using three conditions which are coastal with conductivity of 4746 µS/cm, industrial (818µS/cm) and NH 4 Cl (550 µS/cm) and the result shows that industrial contaminant gives a smallest LCvalue of 327.6 mA with the lesser degradation [11].…”
Section: Introductionmentioning
confidence: 99%